Pengaruh Gaya Kepemimpinan terhadap Pengambilan Keputusan Berbasis Risiko: Perbandingan antara Pendekatan Manajerial dan Leadership di SMAN 1 Karanganyar Demak - Eny Junyanti; Ika Septiana (Universitas Maritim AMNI Semarang, 2024)
This study investigates the influence of leadership styles on risk-based decision-making, comparing managerial and leadership approaches at SMAN 1 Karanganyar Demak. As educational environments become increasingly complex, school leaders face challenges that necessitate effective decision-making, particularly in risky situations. The research aims to identify how different leadership styles impact decision outcomes and the involvement of stakeholders. Utilizing a mixed-methods approach, data were collected through surveys and interviews with teachers and school administrators. Findings indicate that transformational leadership significantly enhances decision-making effectiveness compared to traditional managerial approaches. The implications of this study suggest that adopting a transformational leadership style can lead to better engagement and improved risk management in schools, ultimately fostering a more conducive learning environment. This research contributes to the existing literature by addressing the gap in comparative studies of leadership styles in educational settings, providing practical recommendations for school leaders to enhance decision-making processes.